Groundwater chemistry and supplementary sources of freshwater in Arid environments : groundwater salinisation, solar desalination & fog collection - Shanyengana, Shanyengana E. (Stellenbosch : Stellenbosch University, 2012)
Thesis (DPhil)--Stellenbosch University, 2002.